Is university sports an advertisement in the higher education market? An analysis of the Hakone long-distance relay road race in Japan - Eiji Yamamura (Osaka University, Institute of Social and Economic Research (ISER), 2015)
A university long-distance relay road race, the Hakone Ekiden, is widely acknowledged as the most popular New Year's sporting event in Japan. The event is held immediately prior to the university application period in Japan. Using Japanese panel data for 2001-2014, this study examined how the Hakone Ekiden race influences the behavior of students preparing for university entrance examinations. The major finding is that the number of applicants for a university is 3% larger when the university participated in the race than when it did not. Further, universities finishing in the top three in the race saw a 4% increase in the number of applicants compared with other universities that participated in the race. A 1% increase in the television viewing rate for the race led to a 1% increase in the number of applicants for the universities participating in the race. It follows that advertising universities on television would be effective in the university market.
Keywords: L83; L82; I29; M37; 330; long-distance relay road race (ekiden); Japan; university market; advertisement; television